Penerapan Sistem Informasi Administrasi Kependudukan (SIAK) sebagai Upaya Meningkatkan Kualitas Pelayanan Administratif di Desa Bakung - Mirani Isniati; Wahib Assyahri (Jurnal Ilmu Sosial dan Humaniora, 2024)
The Bakung village government has organized population administration services by implementing the Population Administration Information System (SIAK). Its implementation is still constrained by the low level of public awareness about the importance of updating population data. This research discusses the implementation of SIAK in Bakung Village. The purpose of this research is to find out how SIAK is implemented in Bakung village and what factors are supporting and inhibiting its implementation. This research is a descriptive qualitative research using the Ambiguity-Conflict Matrix Model theory. The informants of this research are the Head of Bakung Village, the Village Registration Officer, and the SIAK service users. The results show that the implementation of SIAK in Bakung village has been running quite optimally, well, conducive, and able to improve the quality of administrative services in Bakung village although there are still problems of brokering practices by certain individuals. Supporting factors are the availability of competent Village Registration Officers as SIAK operators, free administrative services, the location of the Bakung Village Head's office that is easily accessible, and the SIAK application that is easily accessed by operators. The inhibiting factors are the lack of public awareness regarding the updating of population data, the existence of brokering practices, an unstable internet network, and the lack of socialization to the community.